Simultaneous Determination of Trace Fluorine and Chlorine in Iron Ore by Combustion-Ion Chromatography (C-IC). (13th October 2021) - Li, Tong; Min, Hong; Li, Chen; Yan, Chenglin; Zhang, Linping; Liu, Shu
Abstract: The determination of trace fluorine and chlorine in iron ore commonly requires complicated and time-consuming pretreatment involving alkali fusion, combustion in bombs, and pyrohydrolysis that prevent analysis of large numbers of samples. In this study, a rapid combustion-ion chromatography (C-IC) method for the simultaneous determination of fluorine and chlorine in iron ore is reported for the first time. The solid sample injection method, combustion time, sample mass, and absorption solution were optimized. The limits of detection for fluorine and chlorine were 0.029 mg g −1 and 0.031 mg g −1, respectively, which were similar to those for GB/T 6730.69-2010. Eight certified reference materials and three iron ore samples were used to evaluate the accuracy and precision of C-IC. The fluorine and chlorine content in the iron ore samples were from 0.086 to 1.773 mg g −1 and 0.050 to 3.10 mg g −1 . The relative standard deviations for fluorine and chlorine were from 0.77% to 4.27% and 1.36% to 3.74%. The recoveries ranged from 95.3% to 104.6% and 91.9% to 104.3%. The results of iron ore samples determined by GB/T 6730.69-2010 and C-IC were in good agreement. C-IC is environmentally friendly and its suitability for automation may improve the analytical throughput.